Report Management and Archiving SystemStudent Learning Outcomes - Noor Anisa Nilam; Tin Rustini (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
This research aims to describe and analyze the management of the e-reportbased learning outcomes assessment program at SMPN 2 Kepung. Data collection uses interview, observation, and documentation techniques. Data analysis uses a qualitative descriptive model. Validity checking is carried out using credibility, transferability, dependability, and confirmability tests.  Theresults of this research indicate that the planning of e-report program activities is as follows. The e-report program is an innovative in-service support from DAPODIK. This plan aims to maintain accountability for assessments, simplify the teacher's task of preparing learning outcomes reports (LHB), make it easier to archive grade data and avoid mistakes in writing report cards.Implementation of activities in the e-report program, especially inputting grades, is carried out by all teachers and the ICT team as e-report admins. When teachers experience difficulties in entering grade data, it is carried out by the guidelines from DAPODIK to maintain assessment accountability and simplify the task of teachers or schools in preparing  LHB (Learning Results Reports), the evaluation of the e-report program is carried out by the Principal and the ICT team by utilizing the homeroom teacher to evaluate the grades that have been included in the e-report. The activities that have been carried out by SMPN 2 Kepung are expected to be able to create a school that is technologically insightful and able to become an example for other schools, especially in the Kediri area